“Remote sensing”- A part of an Applied Physics - Shah, Arbind Kumar (Himalayan Physics, 2015)
Physics is the most fundamental of all the sciences & scientific developments or technologies. Physics is also behind the modern technologies such as internet & mobile, whereas applied physics does the role of their application to modern technologies. Applied physics describes the laws & phenomenon of nature with their application in different fields like: Physics of imaging, Atmospheric Physics, Nanotechnology, Remote Sensing etc. The Remote Sensing (R. S.) technology is discussed in detail through this paper. The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 102-108